Implementasi Peran Guru Penggerak Dalam Menggerakkan Komunitas Belajar Di SD Negeri 36 Lubuklinggau - Irmansa; Nur Sasongko, Rambat; Somantri , Manap (Manajer Pendididikan, 2024)
This study aims to describe the implementation of the role of the driving teacher in mobilising the learning community at Public Elementary School 36 Lubuklinggau. The roles in question are learning leader, activator of the community of practice, coach for other teachers, collaborator between teachers, and realising student leadership. This research is a qualitative study using interviews, observation and documentation for data collection. The stages of data management began with data collection, reduction, and conclusion. The conclusion of the research is that the driving teacher has implemented all of his roles, namely as a learning leader, a community of practitioners, a coach for other teachers, a collaborator between teachers and a teacher who embodies student leadership to move the learning community in various forms such as initiators in curriculum preparation, providing coaching to other teachers, initiating various activities in the learning community, involving students in classroom and school leadership